Preparation of loaves with addition of ora-pro-nobis flour (Research, Society and Development, 2023)
Pereskia aculeata, popularly known as ora-pro-nobis, is a plant that can be incorporated in different ways in cooking and healthy eating. The aim of this work was to prepare loaves with partial replacement of wheat flour by ora-pro-nobis, evaluating physical-chemical characteristics of the products obtained. The standard loaf had wheat flour, salt, sugar, margarine, biological yeast, egg and water as ingredients. In the others, 2.5, 5 and 10% of the wheat flour was replaced by flour made from ora-pro-nobis leaves. Of the color attributes, the lowest values of luminosity and the color attribute a* evaluated in the loaf crust and crumb stand out. The loaves did not differ significantly in terms of weight, but the formulations with higher amounts of ora-pro-nobis flour had lower volume, which also resulted in higher density and lower specific volume of the products. The addition of ora-pro-nobis flour provided an increase in ash, protein and dietary fiber contents, to the detriment of digestible carbohydrate contents and caloric value of bread formulations, in addition to conferring higher levels of phenolic compounds and antioxidant capacity to breads. It is concluded that the addition of ora-pro-nobis flour in the loaf bread formulation causes changes in both color and volume compared to a standard formulation. However, even in concentrations of up to 10%, the addition of ora-pro-nobis flour results in a good-looking bread, with adequate technological characteristics, enriched with minerals, proteins and fibers, and with a high antioxidant capacity.